Género y rol iniciador en las rupturas sentimentales: diferencias en el afrontamiento - Sánchez-Porro, David (2024)
Romantic breakups involve great psychological and emotional suffering. However, there are factors that allow subjects to achieve adequate well-being. The Dual Process Model proposes two types of tasks (loss-oriented and life-restoration-oriented) to be performed in order to cope with a breakup. Our aim is to analyse the differences in the use of these strategies depending on the gender of the individuals and their role at the onset of the breakup. The results conclude that women cope with breakups through restorative strategies. In terms of the initiator role, when the breakup is produced by mutual decision, mainly loss-focused strategies are used.